2014
DOI: 10.4155/ppa.14.45
|View full text |Cite
|
Sign up to set email alerts
|

Approaches Targeting the FGF–FGFR System: a Review of the Recent Patent Literature and Associated Advanced Therapeutic Agents

Abstract: Fibroblast growth factor receptors (FGFRs) and associated ligands (FGFs) are a family of well-validated targets for therapeutic interventions notably in cancer diseases in relation to their prominent roles in cell growth, survival, differentiation and angiogenesis. This patent review encompasses all different approaches (modulators of FGF or FGFR expression, anti-FGF antibodies, anti-FGFR antibodies, FGF traps, tyrosine-kinase (TK) inhibitors, allosteric modulators) used to block completely or partially the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Mutations were found in 5 of 15 tumors. PIK3CA mutations were identified in 3 tumors, 2 of which also harbored mutations in fibroblast growth factor receptor (FGFR) family members.This is an interesting finding, because phosphatidylinositol 3-kinase (PI3K) inhibitors and FGFR inhibitors are currently in development [50,51]. In the study of Ang et al, an activating mutation of vascular endothelial growth factor receptor 2 (VEGFR2), was found [49], and in another study using immunohistochemistry, VEGF-C was reported to be strongly expressed in NECB [52].…”
Section: Future Perspectivesmentioning
confidence: 94%
“…Mutations were found in 5 of 15 tumors. PIK3CA mutations were identified in 3 tumors, 2 of which also harbored mutations in fibroblast growth factor receptor (FGFR) family members.This is an interesting finding, because phosphatidylinositol 3-kinase (PI3K) inhibitors and FGFR inhibitors are currently in development [50,51]. In the study of Ang et al, an activating mutation of vascular endothelial growth factor receptor 2 (VEGFR2), was found [49], and in another study using immunohistochemistry, VEGF-C was reported to be strongly expressed in NECB [52].…”
Section: Future Perspectivesmentioning
confidence: 94%
“…Finally, FGFR1 has a crucial feature of undergoing rapid internalization, predominantly through clathrin-mediated endocytosis, and subsequent sorting to lysosomes (40), which should ensure efficient drug release from the internalized antibody-drug complexes (44). Recently, the first ADC therapy has been proposed for FGFR2-positive cancer patients, which inhibited tumor growth in xenograft models (45,46). In this study, we report the selection and detailed characterization of a novel internalizing anti-FGFR1 antibody in the scFv-Fc format, named scFvD2-Fc, and its use for targeting FGFR1-expressing lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the peptide comprising the amino acid sequence FGF2 impaired the interaction of FGF2 with FGFR1 [125] and similar peptides were successfully employed to specifically deliver antiblastic drugs to FGFR-overexpressing tumor cells [126]. In addition, vaccination against FGFR1 showed antitumor activity in vivo [127] and anti-FGFR neutralizing antibodies blocked FGF2-mediated angiogenesis in vivo [113,[128][129][130].…”
Section: Preventing Fgf/fgfr/co-receptor Interactionsmentioning
confidence: 99%
“…One of the most exploited approaches for the design of inhibitors of the FGF/FGFR system is based on the production of neutralizing anti-FGF antibodies [103,113] and the search for natural and synthetic FGF binders that sequester the growth factor in the extracellular compartment, thus acting as FGF traps [114,115]. Natural FGF binders (Table 2) have been identified in the ECM and body fluids.…”
Section: Preventing Fgf/fgfr/co-receptor Interactionsmentioning
confidence: 99%